Evaluating the Automatic Chord Estimation and Alignments tasks needs using metrics from a code challenge - Silva, Valter Jorge da; Cabral, Giordano Ribeiro Eulalio (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2021: Anais do XVIII Simpósio Brasileiro de Computação MusicalDO - 10.5753/sbcm.2021.19425, 2021)
Automatic Chord Estimation is a subject of Music Information Retrieval who tries to extract the chords of a song in an usable manner. In the last year, many reseachers tried to overperform the quantitative metrics, but the results lack reprodutibility by who needs them, musicians. In this article, we reviewed the state of art of some of this areas and performed a code Challenge who was evaluated by some of the MIREX metrics and by musicians. Then, with this results, we evaluated the need of evolution on the Estimation task and on the Alignment Task of the MIR area.